PANDANGAN PEMILIK BADAN USAHA ISLAM TERHADAP AKUNTABILITAS DAN MORALITAS - Nurhidayah Chairany Permatasari; Nurul Hasanah Uswati Dewi (STIE Perbanas Surabaya, 2011)
In this accounting, it is aimed at providing economic information that is used as one basis fordecision making. Many academics and practitioners tend to ignore that accounting is also amedia for accountability. It is shown from the widespread practice of earnings managementin various economic entities. Islamic accounting is considered a new discourse in the scienceof stating the consistency of accounting for accounting purposes as a media ofaccountability. Such condition enables this researcher to conduct research in deep analysison the view of the owner of a Islamic business entity for the aspects of accountability andmorality. This research is a qualitative research using phenomenological approach which isto examine the awareness of one's perspective about things. This study used a simplequalitative analysis of the process of data reduction, data display, and conclusion drawing.Views of the owner of a business entity towards accountability and morality of Islam are fair.It is also the fact that they do not regard the abuse of trust and responsibility is a naturalthing. It is assumed that accountability and morality are important and they should beimplemented. With a view from the respondents, it is believed that Islamic accounting isproved to be a suitable alternative for solving the problem of accountability and morality ofconventional accounting